Therapeutic effects of children with refractory epilepsy after vagus nerve stimulation in Taiwan - Sung-Tse Li; Nan-Chang Chiu; Kun-Long Hung; Che-Sheng Ho; Yung-Ting Kuo; Wen-Hsiang Wu; Chuan-Yu Wang; Yung-Ting Kuo; Huei-Shyong Wang; Kuang-Lin Lin; Po-Cheng Hung; Ying-Chao Chang; et al. (Pediatrics and Neonatology)
Background: Vagus nerve stimulation (VNS) is used as an add-on treatment for epilepsy. This study aimed to use Taiwanese nationwide registry data to analyze the therapeutic effects of VNS in children with refractory epilepsy (RE) and try to explore predictive factors of VNS treatment effectiveness. Methods: This retrospective study collected data from December 2007 to December 2014. Patient variables included gender, age, VNS implantation date, epilepsy duration, seizure frequency, seizure type, etiology, and antiepileptic drug (AED) history. We divided patients into three groups: Group I as seizure frequency >80 times per month, Group II as seizure frequency 24–80 times per month, and Group III as seizure frequency <24 times per month. Multivariate regression analysis was performed to determine predictors of seizure frequency reduction after VNS treatment. Results: A total of 80 patients were included in this study. Three or more AED types were prescribed for 61 (77.1%) patients. Seizure frequency decreased significantly at 12 and 24 months after VNS treatment. The mean seizure reduction rates were 44.6% and 50.1% at 12 and 24 months after VNS treatment, with the difference between them reaching statistical significance (p = 0.001). In multivariate linear regression, high seizure frequency (Group I) was a positive predictor of seizure frequency reduction (p < 0.001). The most common complication was coughing (eight patients, 10%) and no patient had early withdrawal or premature termination of VNS use due to complications. Conclusion: VNS is an effective palliative treatment for children with RE for different seizure types. Seizure reduction rate at 24 months after VNS was better than at 12 months after VNS. High seizure frequency can be regarded as a positive predictor for seizure frequency reduction in children with RE treated with VNS.